POLITENESS MAXIM OF MAIN CHARACTER IN SECRET FORGIVEN - Sang Ayu Isnu Maharani (Jurnal Bahasa Lingua Scientia, 2017)
Maxim of Politeness is an interesting subject to be discussed, since politeness has been criticized from our childhood. We are obliques to be polite to anyone either in speaking or in acting. Somehow we are manage to show politeness in our spoken expression though our intention might be not so polite. For example we must appriciate others opinion although we feel objection toward the opinion. In this article the analysis of politeness is based on maxim proposes by Leech. He proposed six types of politeness maxim. The discussion shows that the main character (Kristen and Kami) use all types of maxim in their conversation. The most commonly used are approbation maxim and agreement maxim